Pengembangan Media Video Animasi “AnimFauna” Guna Meningkatkan Minat Belajar Siswa Kelas III SD Materi Metamorfosis Hewan - Aulia Rachma Sari; Novi Nitya Santi; Widi Wulansari (Lembaga Yasin AlSys, 2026)
Although science education in elementary schools has received attention in various studies, research that specifically develops innovative visual media to explain abstract biological processes in classrooms with limited facilities remains relatively limited. This study aims to develop a 2D animated learning video medium named “AnimFauna” that is valid, practical, and effective in improving third-grade elementary school students’ learning interest and outcomes in animal metamorphosis material. This study used a mixed quantitative and qualitative approach with a research and development (R&D) method based on the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The study involved 42 third-grade students of SDN Kayenlor selected through purposive sampling. Data were collected through expert validation sheets, teacher and student response questionnaires, and pretest-posttest evaluation tests, and were then analyzed using Aiken’s V index, descriptive percentages, and N-Gain scores. The results showed that the “AnimFauna” medium was highly valid, with a material expert validation score of 0.96 and a media expert score of 0.75. This medium was also highly practical, as indicated by a practicality level of 100% based on teacher responses and 98.8% based on student responses. In addition, the “AnimFauna” medium was proven effective in improving students’ learning outcomes, with an average N-Gain score of 0.85, which falls into the high category. These findings contribute to the development of visually dynamic digital learning media in elementary school science learning, particularly in animal metamorphosis material. The conclusion of the study confirms that the use of 2D animated videos can serve as an effective alternative learning medium to help students understand abstract biological concepts more concretely. The implications of this study include theoretical contributions to the development of digital pedagogy and practical implications for teachers and educational institutions in designing contextual learning multimedia suited to the characteristics of elementary school students.